An Investigation of Indigenous Knowledge and Institutions Contributing to Natural Forest Conservation in Yayo and Gechi Woreda, Illuababor Zone, Oromia National Regional State, South West Ethiopia (Global Journal of Human-Social Science, 2017)
Abstract not found
Keywords: indigenous knowledge and institutions; natural forest conservation; yayo and gech woreda